Deep Brain Stimulation of Medial Dorsal and Ventral Anterior Nucleus of the Thalamus in OCD: A Retrospective Case Series. - Mohammad Maarouf; Clemens Neudorfer; Faycal El Majdoub; Doris Lenartz; Jens Kuhn; Volker Sturm (PLoS ONE, 2016)
The current notion that cortico-striato-thalamo-cortical circuits are involved in the pathophysiology of obsessive-compulsive disorder (OCD) has instigated the search for the most suitable target for deep brain stimulation (DBS). However, despite extensive research, uncertainty about the ideal target remains with many structures being underexplored. The aim of this report is to address a new target for DBS, the medial dorsal (MD) and the ventral anterior (VA) nucleus of the thalamus, which has thus far received little attention in the treatment of OCD.In this retrospective trial, four patients (three female, one male) aged 31-48 years, suffering from therapy-refractory OCD underwent high-frequency DBS of the MD and VA. In two patients (de novo group) the thalamus was chosen as a primary target for DBS, whereas in two patients (rescue DBS group) lead implantation was performed in a rescue DBS attempt following unsuccessful primary stimulation.Continuous thalamic stimulation yielded no significant improvement in OCD symptom severity. Over the course of thalamic DBS symptoms improved in only one patient who showed "partial response" on the Yale-Brown Obsessive Compulsive (Y-BOCS) Scale. Beck Depression Inventory scores dropped by around 46% in the de novo group; anxiety symptoms improved by up to 34%. In the de novo DBS group no effect of DBS on anxiety and mood was observable.MD/VA-DBS yielded no adequate alleviation of therapy-refractory OCD, the overall strategy in targeting MD/VA as described in this paper can thus not be recommended in DBS for OCD. The magnocellular portion of MD (MDMC), however, might prove a promising target in the treatment of mood related and anxiety disorders.